Teacher Perception of Principal Behaviors A Research Study - Richardson, Michael D. ([Washington, D.C.] : Distributed by ERIC Clearinghouse, 1992)
Findings of a study that investigated teachers' perceptions of the most desirable characteristics of principal behavior are presented in this paper. An instrument used to measure employees' perceptions of business manager characteristics (Kouzes and Posner 1987) was adapted to the educational setting and completed by 1,225 teachers in 4 states. Findings indicated that teachers' rankings of their principals were similar to business employees' rankings of their managers. Both groups said that honesty was the most desirable and necessary characteristics for managers and principals. Other highly rated characteristics included "forward-looking,""inspiring,""caring," and "competent." One figure and two tables are included. (Contains 10 references.) (LMI)
ERIC Note: Paper presented at the Annual Meeting of the Mid-South Educational Research Association (Knoxville, TN, November 10-13, 1992).
May also be available online. Address as at 14/8/18
Microfiche.
Keywords: Administrator Characteristics; Administrator Effectiveness; Administrator Role; Elementary Secondary Education; Leadership; Leadership Qualities; Principals; Teacher Administrator Relationship; Teacher Attitudes; Speeches/Meeting Papers; Reports, Research